Co-Teaching in Health Sciences in Higher Education - Dhar, Arpana (Curtin University, 2019)
This is the first study to expansively investigate students’ and co-teachers’ perceptions and experiences of co-teaching in a higher education environment. The instrument developed, Co-teaching Perception and Experience Survey (CPES), provides a tool to allow evaluation and analysis of co-teaching settings in other higher education institutes. The outcomes identified in this research study will help administrators and policy makers make informed decisions before implementing co-teaching and thus provide students and co-teachers better learning and teaching experiences.